KECERDASAN INTRAPERSONAL DAN SIKAP NASIONALISME TERHADAP PENGUASAAN KONSEP SEJARAH - Wahyu Setianingsih; Nani Hanifah (Herodotus: Jurnal Pendidikan IPS, 2019)
This research is a kind of survey and aims to find out and analyze empirically the effects of intrapersonal intelligence and attitude of nationalism towards student’s conceptual mastery in History. The observed population of this research is students from state senior high schools in West Jakarta. The sample was gained through simple random sampling, which means that the researcher mixed the subjects in the population so that they will be considerably the same. The results of this research are: There are significant effects of intrapersonal intelligence and attitude of nationalism altogether towards student’s conceptual mastery in History. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 58.739; There is a significant effect of intrapersonal intelligence towards student’s conceptual mastery in History. It is proved by Sig.= 0.000 < 0.05 and tobserved = 6.460; There is a significant effect of attitude of nationalism towards student’s conceptual mastery in History. It is proved by Sig.= 0.002 < 0.05 and tobserved = 3.254. It means that the student’s conceptual mastery in History could be improved if teachers would endorse student’s intrapersonal intelligence besides his/her attitude of nationalism.